Role of structural hydroxyl groups in enhancing performance of electrochemically-synthesized bilayer V2O5. (November 2018) - Tepavcevic, Sanja; Connell, Justin G.; Lopes, Pietro P.; Bachhav, Mukesh; Key, Baris; Valero-Vidal, Carlos; Crumlin, Ethan J.; Stamenkovic, Vojislav R.; Markovic, Nenad M.
Abstract: Nanostructured electrode materials represent a promising path forward to dramatically improving the performance of both Li-ion and beyond Li-ion battery systems; however, difficulties in characterizing the structural and electrochemical changes that take place in nanoscale systems, which are often poorly crystalline or amorphous, make it difficult to develop design rules for synthesizing new materials with optimal performance. Bilayered vanadium oxide-based materials (BL-V2 O5 ) are an ideal platform for understanding the underlying physicochemical properties that determine capacity in nanomaterials, with electrochemically-synthesized V2 O5 (EC-V2 O5 ) exhibiting particularly high capacities. In this work we provide evidence that the source of high practical capacity in EC-V2 O5 is the presence of "structural hydroxyl groups" that are an intrinsic feature of the electrochemical synthesis method. Using both in situ and ex situ characterization methods, we demonstrate that structural OH species are highly stable and persist in the structure during reversible cycling. We hypothesize three important roles for structural OH groups: they maintain a sufficient interlayer spacing to allow the physical diffusion of cations over multiple cycles; they maintain a consistent solvating environment in the bilayer regardless of structural H2 O content; and they reduce the symmetry of vanadium polyhedra to favor electron transfer over pseudocapacitive adsorption, making it possible to access close to theoretical capacity. These insights have broad implications for understanding the performance of a variety of hydrated oxide systems, and indicate that the formation of covalently-bound hydroxyoxide species can lead to further improvements in the performance of nanoscale materials. Graphical abstract: fx1 Highlights: Electrochemically-synthesized V2 O5 shows high performance for beyond Li-ion systems. Structural OH is an intrinsic feature of electrochemically-synthesized cathodes. Much greater (electro)chemical stability of structural OH groups vs. structural H2 O. Bilayer stabilization by structural OH leads to enhanced capacity/cyclability.